Case Report: Spontaneous Rupture of Hepatic Hemangioma - Pan, Bing; Lyu, Shao-Cheng; He, Qiang (Frontiers in Medicine, 2022)
Background: Hepatic hemangioma (HH) is congenital vasal malformation, seemed as the most probable benign liver neoplasm, composed of masses of blood vessels that are anomalous in arrangement and size. In most cases, hepatic hemangioma is asymptomatic, and patients have an excellent prognosis. According to research, the location and size of the mass are correlated with the symptoms and complications. Reports of spontaneous rupture of hepatic hemangioma have been less reported in the literature. In this emergency condition, dynamic contrast-enhanced CT scanning, especially triple phase CT with delayed imaging, is preferred. Case Presentation: In here, we presented two middle-aged female patients with spontaneous rupture of hepatic hemangioma in our hospital. Following accurate diagnosis of enhanced CT and emergency surgery, they recovered well and were discharged from the hospital. Conclusions: Appropriate imaging studies especially enhanced CT, and emergency surgery are indispensable for patients with spontaneous rupture of hepatic hemangioma. As a surgeon, we needly pay attention to asymptomatic patient with hepatic hemangioma.